ANALISIS METODE PENGAMBILAN HUKUM MAJELIS HAKIM DALAM MENETAPKAN NAFKAH MADLIYAH (Studi Kasus Putusan MA Nomor. 295K/AG/2000) - Dalimunthe, Mardiah; Prasetiya, Nurul Huda (Universitas Muhammadiyah Ponorogo, 2023)
This study (Case Study of Supreme Court Decision No. 295k/Ag/2000) intends to learn more about the legal procedure the panel of judges used to determine madliyah maintenance. The key data sources used in this study were the Qur'an and hadith, Supreme Court Decision No. 295k/AG/2000, and Law Number 23 of 2002 about Child Protection. The research's method was descriptive qualitative. Books and other forms of literature are examples of secondary data sources. The findings demonstrated that the Supreme Court of the Republic of Indonesia's decision No. 295 K/AG/2000 in determining madliyah maintenance with various decisions in determining the amount of child custody fees, adding each year in accordance with the defendant's capacity as a husband adjusted by the Panel of Judges with the demands of the plaintiff as a wife. In the Supreme Court's Decision No. 295 K/AG/2000, where the judges made their decision using a combination of jurimetry and the idea of maslahah, madliyah maintenance was determined.